NATURAL DIET OF PENAIED PRAWNS IN THE COASTAL WATERS OF MUMBAI - Deshmukh, V. D.; Sawant, M. S.; Mane, S. J.; Hule, A. S. (Journal of Indian Fisheries Association, 2006)
Foregut contents of eight commercially important species of penaeid prawns namely Penaeus merguiensis, Metapenaeus affinis, M. monoceros, M.Â brevicornis, Parapenaeopsis stylifera, P. lwrdwickii, P. ,r,’culptilis and SolenoceraÂ crassicornis were investigated from inshore, nearshore and offshore fishingÂ grounds ofMumbai. Feeding intensity and index of preponderance (IP) of theÂ dietary items were compared statistically for the species, sexes, fishing areasÂ and maturity condition of females. AU the species except M. monoceros and P.Â sculptilis showed that females were better fed than males. The feeding intensityÂ in the three depth-zones was different for M. affinis, M. brevicornis, M.Â monoceros, P. hardwickii and S. crassicornis, and un.iform for P. merguiensis, P. stylifera and P. sculptilis. Acetes spp., prawn remains, polychaetes, benthicÂ crustaceans, foraminifers and fish remains were the important food items ofÂ the prawns. Dietary comparison between the two sexes of the species did notÂ show any difference, but mature females of M. monoceros and P. sculptilis hadÂ different diets. Comparison of food items for all the species together showedÂ significant difference between the three areas. Crustacean diet was theÂ favourite in the inshore and nearshore, and polychaetes in the offshore waters.Â All the species except P. hardwickii showed difference in their dietaryÂ composition in the three depth-zones. It is concluded that these coexistingÂ species are primarily carnivorous and exhibit diverse food preferences inÂ different depth-zones by browsing on interstitial organisms, chasingÂ epipelagic prey, raptorial predation, scavenging on dead organisms orÂ adopting different temporal abundance to avoid inter-specific competition forÂ food. Keywords: Foregut, penaeid prawns, diet inter-specificity